Finite Element Analysis of Double Arc and Quadruple Arc Spiral Bevel Gear based on Abaqus - Ren Zhongyi; Zhao Qinghua; Duan Jianzhong; Jiang Biqiong (Jixie chuandong)
The quadruple arc spiral bevel gear is a new type of gear with quadruple arc tooth profile applied to the spiral bevel gear. The three-dimensional model is built in Solid Works based on the tooth surface equation of spiral bevel gear with circular arc tooth profile. The static finite element analysis is carried out by using a pair of teeth based on Abaqus. Compared with the double arc spiral bevel gear,it is concluded that the load capacity of quadruple arc spiral bevel gear is 30% higher than that of double arc spiral bevel gear.